STUDY OF MICROELEMENT IMBALANCES IN INTESTINAL HELMINTHIASIS AND IMPROVEMENT OF THEIR CORRECTION - Shodmonov Iskandar Sergeyevich, (TADQIQOTLAR, 2025)
Intestinal helminthiasis remains a common parasitic disease worldwide and is associated  not  only  with  gastrointestinal  manifestations  but  also  with  systemic metabolic  disturbances.  Chronic  helminth  infections  can  disrupt  microelement homeostasis  due  to  impaired  intestinal  absorption  and  competition  for  essential micronutrients.